2008
DOI: 10.1111/j.1442-2050.2008.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

The esophageal remnant after gastric interposition

Abstract: Gastric interposition is usually considered the reconstruction of choice following esophageal resection. However, a number of reports show that esophagectomy followed by a gastric transplant is associated with poor quality of life and significant reflux esophagitis in the esophageal remnant. The aim of this work is to review the factors affecting the mucosa of the esophageal remnant when using the stomach. A Medline was conducted. Additional references and search pathways were sourced from the references of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…In contrast, postoperative patient‐related variables as independent factors affecting survival have been scarcely suggested. During the postoperative period, several side effects of esophagectomy can merge, including onset of postoperative complications, surgical stress, impaired inflammatory response, and malnutrition as a consequence of gastric volume reduction, delayed food intake, impaired gastric emptying, dysphagia, and reflux 6–9 . The expected end‐results of this multifaceted process can lead to a strong impairment of the immunologic system that may adversely impact on the oncologic outcome 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, postoperative patient‐related variables as independent factors affecting survival have been scarcely suggested. During the postoperative period, several side effects of esophagectomy can merge, including onset of postoperative complications, surgical stress, impaired inflammatory response, and malnutrition as a consequence of gastric volume reduction, delayed food intake, impaired gastric emptying, dysphagia, and reflux 6–9 . The expected end‐results of this multifaceted process can lead to a strong impairment of the immunologic system that may adversely impact on the oncologic outcome 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in gastric acid secretion after gastric-tube reconstruction can effectively prevent the occurrence of reflux esophagitis [23, 24]. (3) The volume of the tubular stomach is smaller than that of the whole stomach (21.4%–47.2% reduction) [25]. Thus, the compression of the stomach by the lungs during coughing or breathing is reduced, which can decrease the duration and amount of reflux [26].…”
Section: Discussionmentioning
confidence: 99%
“…There is no recommendation for surveillance post esophagectomy and reports of a second cancer developing in the cervical esophageal remnant harboring Barrett's are rare. [12][13][14] Alterations in functional outcome after esophagectomy may also be overemphasized. Williams et al in a careful functional analysis of patients following transhiatal esophagectomy for HGD found that the vast majority are doing quite well.…”
Section: Morbidity Mortality and Functional Outcome Of Esophagectommentioning
confidence: 97%